2015
DOI: 10.4102/sajbm.v46i3.99
|View full text |Cite
|
Sign up to set email alerts
|

Advertising vs. R&D: Relative effectiveness on brand equity

Abstract: This study examines whether advertising can contribute directly to brand equity and, if it can, determines how much value advertising can deliver to brands and firms using the secondary data from various sources. The findings show that advertising can not only work to improve market performance measures but also to develop and maintain brand equity. R&D is also found to positively affect brand equity. With regard to the relative effectiveness of advertising and R&D, R&D is more effective than advertising in co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 90 publications
1
3
0
1
Order By: Relevance
“…In terms of the positive effect of MSD, this study supports the findings of Chu and Keh (2006), Peterson and Jeong (2010), Jeong (2015), and Koçan (2017), but not in relation to the negative effect of R&D on brand value.…”
Section: Discussion and Concluding Remarkssupporting
confidence: 80%
See 1 more Smart Citation
“…In terms of the positive effect of MSD, this study supports the findings of Chu and Keh (2006), Peterson and Jeong (2010), Jeong (2015), and Koçan (2017), but not in relation to the negative effect of R&D on brand value.…”
Section: Discussion and Concluding Remarkssupporting
confidence: 80%
“…In financial terms, some studies exploring brand value have focused on its relationship with R&D and advertising expenditures: Chu and Keh (2006), Peterson and Jeong (2010), Jeong (2015), and Koçan (2017) all found that expenditure on R&D, promotion, and advertising, including administration, exert a significant and positive affect on brand value; Eng and Keh (2007) found that advertising and brand value improved future accounting returns.…”
Section: Brand Valuementioning
confidence: 99%
“…Compared with established firms in a market, potential entrants may also advertise more to convince prospective buyers that their products are as good, if not better, than the products of established sellers [50]. Second, it can establish brand loyalty in the minds of consumers [51].…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…These activities influence consumers' brand perceptions, thus achieving the goal of enhancing brand value (Cobb-Walgren et al, 1995;Keller, 2003). Prior research has demonstrated the impact of investments in brand activities such as advertising, research and development, and promotion on brand value (Chaudhuri, 2002;Chu & Keh, 2006;Jeong, 2015). Firms that invest in ESG to gain a good reputation, thereby increasing brand value, exhibit a 'reputation spillover effect'.…”
Section: Hypothesis Developmentmentioning
confidence: 99%